Phosphinine‐Based Ligands in Gold‐Catalyzed Reactions. Issue 37 (21st May 2019) - Rigo, Massimo; Habraken, Evi R. M.; Bhattacharyya, Koyel; Weber, Manuela; Ehlers, Andreas W.; Mézailles, Nicolas; Slootweg, J. Chris; Müller, Christian
Abstract: A series of substituted phosphinines, 1‐phosphabarrelenes and 5‐phosphasemibullvalenes were synthesized and evaluated for their potential application as ligands in homogeneous catalytic reactions. While their buried volume (% V bur ) was calculated to get insight into the steric properties, [LNi(CO)3 ] complexes were prepared in order to determine the corresponding Tolman electronic parameter. ETS‐NOCV (extended‐transition‐state natural orbital for chemical valence) calculations on [LAuCl] complexes further allowed an estimation of the σ‐ and π‐contributions to the L− M interaction. Au I coordination compounds of selected examples were prepared and characterized by single crystal X‐ray diffraction. Finally, the three classes of P III compounds were successfully used in the Au I ‐catalyzed cycloisomerization of N ‐2‐propyn‐1‐ylbenzamide, showing very good activities and selectivities, which are comparable with the reported data of cationic phosphorus‐based gold catalysts. Abstract : Powerful ligands : The ligand properties of a series of phosphinines as well as related 1‐phosphabarrelenes and 5‐phosphasemibullvalenes have been evaluated both experimentally and computationally. The corresponding Au I complexes have been structurally characterized and successfully used as precatalysts in the Au I ‐catalyzed cycloisomerization of N ‐2‐propyn‐1‐ylbenzamide.